The Compromise Condition for High Performance of the Single Silicon Heterojunction Solar Cells - Youngseok Lee; Vinh Ai Dao; Sangho Kim; Sunbo Kim; Hyeongsik Park; Jaehyun Cho; Shihyun Ahn; Junsin Yi (International Journal of Photoenergy)
For optimum performance of the hydrogenated amorphous silicon/crystalline silicon (a-Si : H/c-Si) heterojunction solar cells, featuring a doping concentration, localized states, as well as thickness of emitter layer are crucial, since Fermi level, surface passivated quality, and light absorption have to be compromised themselves. For this purpose, the effect of both doping concentration and thickness of emitter layer was investigated. It was found that with gas phase doping concentration and emitter layer thickness of 3% and 7 nm, solar cell efficiency in excess of 14.6% can be achieved. For high gas phase doping concentration, the degradation of open-circuit voltage as well as cell efficiency was obtained due to the higher disorder in the emitter layer. The heavily doped along with thicker in thickness of emitter layer results in light absorption on short wavelength, then diminishing short-circuit current density.